Use of task-shifting to scale-up child mental health services in low-resource Ugandan schools: role of contextual factors on program implementation - Huang, Keng-Yen; Nakigudde, Janet; Brotman, Laurie Miller (Implementation Science, 2015)
Children in Sub-Saharan Africa (SSA) are burdened by significant unmet mental health needs, but this region has limited access to mental health services to address these needs. Despite the success of numerous interventions for promoting child mental health, most evidencebased programs (EBPs) are not available in SSA. This study utilizes a task-shifting strategy and trains teachers as community health workers (CHWs) to utilize EBP strategies and provide basic child mental health services in schools. This paper focuses on two implementation objectives: 1) investigating the transportability of an EBP (ParentCorps-a school-based mental health program) from a developed country to a SSA country-Uganda by evaluating quality of implementation; and 2) studying the influences of contextual factors (i.e., agency setting, individual characteristics) on implementation processes and outcomes (e.g., CHWs’ level of engagement and utilization of EBP strategies).
Keywords: Child mental health services; Low-resource Ugandan schools